2007
DOI: 10.1016/j.bbrc.2007.06.175
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the multidrug efflux regulator AcrR from Escherichia coli

Abstract: The Escherichia coli AcrR represses transcription of the acrB gene, which encodes the multidrug efflux pump AcrB that extrudes a wide variety of toxic compounds, by binding its target operator DNA. Fluorescence polarization was performed using purified, recombinant AcrR that contains a 6xHis tag at the C-terminus and a fluorescein-labeled 28-base pair oligonucleotide bearing a predicted palindrome (IR) operator sequence. Binding of AcrR to the predicted IR sequence occurred with a dissociation constant (K D ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
101
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 29 publications
1
101
0
1
Order By: Relevance
“…8). Such a phenomenon has been previously observed with the crystal structure of QacR simultaneously bound to two ligands, proflavin and ethidium, 19 and has been predicted through biochemical analysis to occur in many other proteins, including AcrR, 22,23 TtgV 24 and MdfA. 25 It has also been reported that the QacR repressor can bind a single ligand in multiple positions, 26 possibly due to the multifaceted nature of this protein.…”
Section: Discussionmentioning
confidence: 62%
“…8). Such a phenomenon has been previously observed with the crystal structure of QacR simultaneously bound to two ligands, proflavin and ethidium, 19 and has been predicted through biochemical analysis to occur in many other proteins, including AcrR, 22,23 TtgV 24 and MdfA. 25 It has also been reported that the QacR repressor can bind a single ligand in multiple positions, 26 possibly due to the multifaceted nature of this protein.…”
Section: Discussionmentioning
confidence: 62%
“…Although these TFRs bind different ligands (many structurally unrelated compounds such as ethidium, proflavin, and rhodamine 6G for AcrR (36), saturated fatty acid-CoA and unsaturated fatty acid-CoA for DesT (39,40), and numerous structurally dissimilar monovalent and bivalent cationic and lipophilic compounds for QacR (41,42)), their ligand-binding cavities are similarly positioned in the ligand-binding domain (28). Ligand binding results in a conformational change of the DNA-binding domain, for which the relocation of ␣6 helix upon ligand binding induces a pendulum-like motion of the DNA-binding domain in TFRs including TetR (43), QacR (41), and DesT (39).…”
Section: Discussionmentioning
confidence: 99%
“…Many genes are under either local or global transcriptional control. For example, the multidrug transporter AcrAB is locally controlled by the transcriptional repressor AcrR in Escherichia coli (10,11) and Salmonella enterica (12) and by global transcriptional activators of the AraC/XylS family, such as MarA, SoxS, and Rob (13)(14)(15).…”
mentioning
confidence: 99%